2016
DOI: 10.1001/jamaoto.2016.1051
|View full text |Cite
|
Sign up to set email alerts
|

Association of Socioeconomic Status and Race/Ethnicity With Treatment and Survival in Patients With Medullary Thyroid Cancer

Abstract: In this population-based study of patients with MTC, black patients were less likely to have lymph node examination following surgery. Furthermore, Hispanic and black patients had poorer overall and disease-specific survival compared with non-Hispanic white patients after accounting for clinical factors. Racial/ethnic disparities exist in the type of treatment as well as outcomes in patients with MTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Guidelines may be needed that define postdetection interventions to limit overtreatment of indolent, small‐sized, papillary carcinomas. Ongoing clinical trials evaluating active surveillance of small papillary thyroid cancers can hopefully inform these guidelines . In addition, educating patients about thyroid cancer overdiagnosis and the risks associated with potential overtreatment of thyroid cancer may allow patients to be more engaged in shared decision making so they can help determine their best course of action …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines may be needed that define postdetection interventions to limit overtreatment of indolent, small‐sized, papillary carcinomas. Ongoing clinical trials evaluating active surveillance of small papillary thyroid cancers can hopefully inform these guidelines . In addition, educating patients about thyroid cancer overdiagnosis and the risks associated with potential overtreatment of thyroid cancer may allow patients to be more engaged in shared decision making so they can help determine their best course of action …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, many other cancers (eg, colorectal, gastric, head and neck, lung, and prostate) have racial/ethnic disparities that show the highest incidence rates in African Americans . Descriptive reports have suggested that these racial/ethnic differences could have arisen from dissimilar access to US‐guided FNA and CT, a manifestation of variances in socio‐economic status and insurance coverage . If this is true, age‐adjusted incidence rates (AAIRs) and odds ratios (ORs) would vary by race/ethnicity primarily in stage I papillary carcinomas that are <40 mm in size.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies note that disparities tend emerge after innovations become more common in clinical practice [15]. Further, a recent study of MTCs note similar rates of thyroidectomy among blacks and whites, but lower odds of lymph node dissection following surgery among blacks compared to whites, after accounting for clinical factors [24]. Similarly, studies of DTCs note comparable use of thyroidectomy and cause-specific survival rates in blacks and whites after controlling for clinical factors [2,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Further, we were not able to capture all the clinical features that may influence a physician's decision to recommend MKIs and determine who may most benefit from chemotherapy [27], including specific MTC tumor markers or detailed clinical information regarding resistance to radiation among patients with DTC. Further, the NCDB only captures patients treated at CoC-accredited facilities, and these patients may not be representative of all patients; however, case characteristics between the current study and a previous study utilizing a population-based registry (Surveillance Epidemiology and End Results) are similar [24]. The precision of our multivariable models estimates are also wide as a result of our modest sample size; however, due to the rarity of MTC and metastatic DTCs, our study contains a relatively large number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Chen also uncovered disparities in medullary thyroid cancer, which is relatively rare but accounts for 14% of thyroid cancer–related deaths. In a JAMA Otolaryngology study published in 2016, she and her colleagues found that black patients were less likely to have a lymph node examination after surgery and that Hispanic and black patients had poorer overall and disease‐specific survival than non‐Hispanic white patients after they had accounted for clinical factors.…”
Section: Applying Previous Researchmentioning
confidence: 99%